2011
DOI: 10.1055/s-0030-1269928
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise as a Therapy Option for Migraine: A Pilot Study

Abstract: Exercise is assumed to have a positive effect on migraine. However, none of the few studies on this topic can prove the expected positive influence of exercise. Therefore, the aim of this pilot study was to develop a training program suitable for migraine patients and to examine its effect on migraine. 16 patients were examined. 8 migraine patients completed a 10-week aerobic running exercise program consisting of 3 workouts per week. The program was developed by sports scientists especially to increase the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
139
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(150 citation statements)
references
References 12 publications
6
139
0
5
Order By: Relevance
“…19 , so the parameters of intensity, frequency and duration of exercise were based on the parameters used for the healthy population 27 . The regular practice of aerobic exercise seems to benefit patients with migraine 17,18,19,20,21,22,23,24 . These benefits could be related to increased production of beta-endorphins 18 or changes in levels of nitric oxide during aerobic exercise 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 , so the parameters of intensity, frequency and duration of exercise were based on the parameters used for the healthy population 27 . The regular practice of aerobic exercise seems to benefit patients with migraine 17,18,19,20,21,22,23,24 . These benefits could be related to increased production of beta-endorphins 18 or changes in levels of nitric oxide during aerobic exercise 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the prophylactic drug therapies, multiple studies have shown benefits of non-pharmacological interventions such as aerobic exercise 17,18,19,20,21,22,23,24 . Exercise of moderate intensity and practiced regularly can promotes muscle relaxation, improved cardiovascular fitness and also reduces the frequency, intensity and duration of headache attacks 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The aerobic exercise is found effective in reduction of the self-rated migraine pain intensity in few reports. [25,26] Interestingly, the rosemary (rosemarinus officinalis) has also been used frequently in migraine patients in Turkey different from the other countries. Although the rosemary therapy is known in 23.6% of patients, tried in 10%, and benefited in 7.3% of headache patients in Turkey, we can not find any literature knowledge about rosemary effect on headache.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of biological rhythms is important in maintaining health, i.e., ultradian (e.g., feeding cycles) [2], circadian (e.g., cycles of sleep, digestive secretions, bowel movements) [3], infradian (e.g., menstrual cycles) [3], and diurnal rhythms (circadian rhythms synchronized with day-night cycle) [4]. Lifestyle behaviors of sleep [5], exercise [6][7][8], mealtime pattern [9] and hydration status [10] are known to independently affect migraine occurrence. Individual-customized daily aerobic exercise, daily scheduled stress management and relaxation techniques, and mindfulnessbased stress reduction prevent migraine [5], while inadequate sleep hygiene, non-restorative sleep, skipping meals, and dehydration can trigger migraine [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%